2019
DOI: 10.4322/dae.2019.050
|View full text |Cite
|
Sign up to set email alerts
|

Uso benéfico de lodo de estações de tratamento de água e de tratamento de esgoto: estado da arte

Abstract: Especialistas atualmente concordam que a abordagem tradicional de gerenciamento de resíduos sólidos com foco no final da etapa do processo produtivo (abordagem linear) não é suficiente num cenário com restrição cada vez maior de recursos naturais e financeiros. Assim, as novas estações de tratamento de água (ETAs) e de esgoto (ETEs) devem ser projetadas levando em consideração a prioridade na gestão e no gerenciamento dos resíduos sólidos, preconizada pela política brasileira, da Europa, do Japão e da China: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The manufacturing of ceramic materials, including common bricks [22], nonstructural and decorative bricks [23], cementfree geopolymers [24], and glazed tiles [25] has found success worldwide when WTS partially replaces natural soils for civil building applications. Research in Brazil has suggested WTS as a material for civil construction [26] and assessed this waste's capacity to provide a variety of products [27], including structural bricks [28]. WTS used in alkaline soils also seems theoretically viable given that it can help restore damaged mining regions by immobilizing inorganic phosphorus in poor soils [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The manufacturing of ceramic materials, including common bricks [22], nonstructural and decorative bricks [23], cementfree geopolymers [24], and glazed tiles [25] has found success worldwide when WTS partially replaces natural soils for civil building applications. Research in Brazil has suggested WTS as a material for civil construction [26] and assessed this waste's capacity to provide a variety of products [27], including structural bricks [28]. WTS used in alkaline soils also seems theoretically viable given that it can help restore damaged mining regions by immobilizing inorganic phosphorus in poor soils [29].…”
Section: Literature Reviewmentioning
confidence: 99%